2007
DOI: 10.1016/j.clinbiochem.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics and clinical utility of an enzymatic method for the measurement of glycated albumin in plasma

Abstract: Objective: The measurement of plasma glycated albumin is particularly useful in the short-middle term monitoring of glycometabolic control in diabetics. The aim of this work is to evaluate a new enzymatic method for the measurement of glycated albumin in plasma, with particular attention to some selected cases and comparison with other relevant tests (fasting plasma glucose, after glucose load, fructosamine, glycated hemoglobin).Design and methods: We have performed a multicenter study by which sample collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
63
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 23 publications
5
63
0
9
Order By: Relevance
“…Results indicated that the GA enzymatic test proved to be reproducible and robust, as reported in previous studies. 5,7 Moreover, the enzymatic method for GA measurement used in the current study showed high accuracy and reproducibility compared with conventional high-performance liquid chromatography methods. 5 Because this method can use an autoanalyzer, rapid and multiple sample determinations can be performed with ease and convenience.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated that the GA enzymatic test proved to be reproducible and robust, as reported in previous studies. 5,7 Moreover, the enzymatic method for GA measurement used in the current study showed high accuracy and reproducibility compared with conventional high-performance liquid chromatography methods. 5 Because this method can use an autoanalyzer, rapid and multiple sample determinations can be performed with ease and convenience.…”
mentioning
confidence: 99%
“…2 Fructosamine and GA levels in healthy human patients and human patients with diabetes have been reported to show strong correlation. 6,7 As such, the current study sought to determine whether this correlation would also hold true for dogs and, if so, whether GA could be used as a substitute for fructosamine in dogs. The data indicated that a strong positive correlation exists between fructosamine and GA in dogs.…”
mentioning
confidence: 99%
“…2 Fructosamine and GA levels in humans and canines have been reported to show strong correlation. 6,8 The current study suggests that this correlation also holds true for cats and that GA can be used as a substitute for fructosamine in cats. Moreover, serum GA appears to be a useful diagnostic indicator to monitor glycemic control in diabetic cats as an alternative to fructosamine.…”
mentioning
confidence: 86%
“…Alternatively, the measurement of GA has been commonly advocated in human diabetic patients and can also provide an index of glycemic control for 1-3 weeks. 3,6,9,10 In addition, a recent study demonstrated that serum GA could substitute for fructosamine with diabetic dogs. 8 As such, the working hypothesis of the current study is that GA could be substituted for fructosamine in diagnosis and treatment monitoring of diabetic cats because GA is a main constituent of fructosamine.…”
mentioning
confidence: 99%
“…We would particularly like to stress the importance of measuring glycated albumin when interpreting HbA 1c measurements could be hampered by certain pre-analytical conditions (e.g., in cases of chronic hemolytic anemia or hemoglobin variants). It is also worth bearing in mind that glycated albumin can be measured with a specific, robust and reliable enzymatic method that overcomes the limitations of the previous fructosamine test [ 84 ]. It could prove extremely interesting to apply this new test in re-assessing the data used to calculate the glycation gap (GG), proposed for the first time by Cohen et al [ 85 ], whose work proved that GG is reproducible.…”
Section: Glycated Albuminmentioning
confidence: 99%